Pengaruh Fraud Triangle Terhadap Kecurangan Laporan Keuangan Pada Dengan Gender Komite Audit Sebagai Pemoderasi - Riandy Aulia Imron Harahap; Fikri, Ahmad Fikri Alamin; Bambang Somantri Wijaya (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This research seeks to analyze the influence of the fraud triangle components namely pressure, opportunity, and rationalization on financial statement fraud, with the gender composition of the audit committee serving as a moderating variable. This study shows that the presence of women on the audit committee plays an important role in minimizing financial statement fraud due to weak organizational control. The study adopts a quantitative approach, utilizing secondary data for its analysis. The research focuses on manufacturing firms operating in cyclical sectors that are listed on the Indonesia Stock Exchange from 2019 to 2023. Samples were selected using purposive sampling, resulting in 65 companies and a total of 325 data points. Logistic regression analysis was employed, as the dependent variable is binary in nature. The findings indicate that both pressure and rationalization have a positive effect on financial statement fraud, whereas opportunity does not. Furthermore, the presence of female members on the audit committee strengthens the relationship between rationalization and financial statement fraud, but does not moderate the relationship between either pressure or opportunity and financial statement fraud.